Complications and Outcomes of Surgically Treated Pediatric Supracondylar Humerus Fractures - Sebastian G. Hahn; Andrea Schuller; Lorenz Pichler; Anna Hohensteiner; Thomas Sator; Oskar Bamer; Britta Chocholka; Manuela Jaindl; Elisabeth Schwendenwein; Bikash Parajuli; Sanika Rapole; Thomas Tiefenboeck; et al. (MDPI AG, 2024)
This study describes the outcome of supracondylar humerus fractures in children using crossed K-wires after closed or open reduction with the medial, lateral or bilateral approach. Patients treated between January 2000 and December 2019 were classified according to the Von Laer classification, complications were classified according to the Sink classification and clinical outcomes were classified according to modified Flynn criteria. In total, 364 patients with a mean age of 5.23 ± 2.45 years were included. The majority were type IV fractures (156; 42.9%) and 94 (60.3%) needed an open reduction for which the medial approach (53; 56.4%) was predominantly used. Overall, of 50 complications (31 using closed reduction, 19 open reduction), 17/50 (34%) needed revision surgery. An excellent clinical outcome was achieved in 348/364 (95.6%) patients. The approach used for open reduction as such had no influence on the complication rate or clinical outcome. For severely displaced fractures, the data showed that an open approach for crossed K-wires tended to result in fewer complications and better clinical outcomes than a closed reduction. If an open reduction is indicated, the required approach (medial, lateral or bilateral) should be primarily selected according to the requirements of the fracture pattern and eventual cosmetic considerations.